An Insight Into the Effect of Organic Amendments on the Transpiration Efficiency of Wheat Plant in a Sodic Duplex Soil - Wang, Xiaojuan; Sale, Peter; Franks, Ashley; Jin, Jian; Krohn, Christian; Armstrong, Roger; Tang, Caixian (Frontiers in Plant Science, 2021)
Transpiration efficiency (TE), the shoot biomass produced per unit of transpired water, is generally considered to be a constant property for a given crop at a given environment. To determine whether deep-banded organic amendments affect the TE of wheat plants and also provide a possible explanation for any change in the TE, two column experiments were carried out under controlled environment conditions. A Sodosol soil with physically constrained subsoils and a well-structured Vertosol, were subjected to treatments including a control, fertilizer nutrients alone and fertilizer-enriched organic amendments. The addition of fertilizer-enriched organic amendments in Sodosol consistently increased the canopy TE, compared to the control and inorganic fertilizer treatments. The instantaneous TE, at the leaf level, was also increased by the organic-based amendments due to greater reductions in stomatal conductance and transpiration rates during periods of moderate water deficit stress and the subsequent recovery from this stress. Shoot N status could not explain the increases in TE following the addition of organic amendments relative to inorganic amendments. The increases in canopy TE were directly associated with increases in the absolute abundance of indigenous Bacillus (R2=0.92, P<0.0), a well-known genus comprising many strains of plant beneficial rhizobacteria, in subsoil below the amendment band. In contrast, there were no differences in the canopy and instantaneous leaf TE values between organic and fertilizer amendments in the Vertosol with a well-structured subsoil. The positive effect of organic amendments on TE in the Sodosol should be attributed to their direct or indirect effect on improving the physical structure or biological properties of the subsoil.